2019
DOI: 10.1253/circj.cj-18-0743
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Exchanged Protein Directly Activated by cAMP (Epac)1-Inhibiting Therapy for Prevention of Atrial and Ventricular Arrhythmias in Mice

Abstract: Background: It has been suggested that protein directly activated by cAMP (Epac), one of the downstream signaling molecules of β-adrenergic receptor (β-AR), may be an effective target for the treatment of arrhythmia. However, there have been no reports on the anti-arrhythmic effects or cardiac side-effects of Epac1 inhibitors in vivo. Methods and Results: In this study, the roles of Epac1 in the development of atrial and ventricular arrhythmias are examined. In addition, we examined the usefulness of CE3F4, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
(47 reference statements)
2
16
0
Order By: Relevance
“…More importantly, increased P wave duration was recently demonstrated to be a potent indicator of paroxysmal AF susceptibility and a discriminator of paroxysmal AF history not only in humans, but also in mice 32 . We thus examined the effects of BO on AF susceptibility in mice in terms of the duration of AF induced by transesophageal burst pacing 22 , 33 35 (Fig. 2 C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, increased P wave duration was recently demonstrated to be a potent indicator of paroxysmal AF susceptibility and a discriminator of paroxysmal AF history not only in humans, but also in mice 32 . We thus examined the effects of BO on AF susceptibility in mice in terms of the duration of AF induced by transesophageal burst pacing 22 , 33 35 (Fig. 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…While a surface ECG was recorded using electrode in a lead-II configuration, a 1.1-French catheter electrode (EPR800; Millar Instruments, Houston, TX, USA) was carefully advanced and fixed at the esophageal position dorsal to the left atrium. Induction of AF was conducted by applying transesophageal atrial burst pacing for 10 s at a stimulation amplitude of 1.5 mA with 10 ms cycle lengths and a pulse width of 3 ms. AF was defined according to the following criteria: (i) loss of P wave, (ii) irregular R-R interval, and (iii) duration greater than 2 s, which have already been adopted for AF in mice induced by rapid transesophageal atrial pacing by us 33 35 and other groups 58 , 59 . Further, after the screening of AF induction based on these criteria by a single technician who was blind to information about the experimental groups, the diagnosis was always re-checked by an expert on cardiac physiology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent functional analyses of genetically engineered mouse models further demonstrated that Epac1 deficiency resulted in reduced susceptibility to atrial fibrillation (the most common sustained cardiac arrhythmia) and ventricular arrhythmia [58]. Consistently, the Epac1-selective inhibitor CE3F4 shortened the duration of the pacing-induced atrial fibrillation and reduced the incidence of sympathetic activation-induced ventricular arrhythmias, suggesting that Epac1 pharmacological inhibition was an effective strategy in the prevention of arrhythmia [78].…”
Section: Atrial and Ventricular Arrhythmiasmentioning
confidence: 91%
“…Although the safety of drugs that act on Epac has not been well-investigated in a cancer setting, their side effects are reported to be minimal when used for cardiovascular diseases. In fact, studies suggest that the use Epac modulators poses a lower risk for heart failure than beta-blockers [157]. Likewise, these drugs have the potential to become alternative pain management medications to opioids due to their lesser complications [25].…”
Section: Implication Of Epac Modulators In Cancer Therapymentioning
confidence: 99%